Study on the SiCp/Al Composites Prepared by Pressureless Infiltration - Wang, Qingping; Min, Fanfei; Wu, Yucheng; Hong, Yu; Liu, Yin; Xu, Chuyang (Asian Journal of Chemistry, 2013)
SiCp/Al composites with high reinforcement content were fabricated by pressureless infiltration of aluminum alloy into porous SiC preform obtained by self-oxidation bonding at low temperature. The microstructure, composition and infiltration mechanism of SiC/Al composites were analyzed by scanning electron microscope, energy dispersion spectrometer and X-ray diffraction. The effects of SiC volume content on the mechanical properties of the composites were also examined. The relative density of the SiCp/Al composite reached 98 %. The reinforcement volume fraction achieved 55-65 % by using bimodal particle distributions. The bending strength ranged from 320 to 342 MPa, depending on the particle size.